2013
DOI: 10.1192/pb.bp.111.037366
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an integrated rapid response psychiatric liaison team on quality improvement and cost savings: the Birmingham RAID model

Abstract: Aims and methodTo evaluate whether the implementation of the Rapid Assessment, Interface and Discharge (RAID) integrated model improves access to psychiatric assessment and reduces cost of health service provision in an acute hospital. Length of hospital stay was calculated using a case-by-case matched control design. Readmission rates were calculated and survival analysis was used to measure endurance in the community following discharge.ResultsIn an acute hospital with 600 beds, the total savings in bed days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 21 publications
1
105
0
Order By: Relevance
“…A number of initiatives have been developed to improve the care of older people with dementia in acute hospitals, including liaison psychiatric services [50,73] or specialist units that combine medical and mental health care for older people [41,44]. Much of the work in this area is AMD, age-related macular degeneration; AMI, acute myocardial infarction; CI, cognitive impairment; DM, diabetes mellitus; HbA1c, glycosylated hemoglobin; LDL-C, low-density lipoprotein cholesterol PWD, people with dementia; QOF, quality of life; VEGF, vascular endothelial growth factor; VI, visual impairment.…”
Section: Models Of Care For Older People With Cognitive Impairmentmentioning
confidence: 99%
“…A number of initiatives have been developed to improve the care of older people with dementia in acute hospitals, including liaison psychiatric services [50,73] or specialist units that combine medical and mental health care for older people [41,44]. Much of the work in this area is AMD, age-related macular degeneration; AMI, acute myocardial infarction; CI, cognitive impairment; DM, diabetes mellitus; HbA1c, glycosylated hemoglobin; LDL-C, low-density lipoprotein cholesterol PWD, people with dementia; QOF, quality of life; VEGF, vascular endothelial growth factor; VI, visual impairment.…”
Section: Models Of Care For Older People With Cognitive Impairmentmentioning
confidence: 99%
“…23,24 In this model, all elements of good liaison and community care can be combined and deployed when needed, and the clinicians in the services also have a more satisfying working relationship with patients with a greater degree of variety than at present. This does not mean that specialist teams are unnecessary, particularly for some in-patients such as those in longer-term rehabilitation, and for other disorders 25,26 where there is much room for improvement, but for acute care an integrated system makes better use of expertise and brings community and hospital services together.…”
Section: Need For Reorganisation Of Community Teamsmentioning
confidence: 99%
“…The RAID model began in December 2009 aiming to deliver mental health services to Birmingham City Hospital acute hospital 7 days per week, 24 hours per day; the aim being to assess individual's mental health. RAID works within the emergency department and inpatient acute wards (Tadros et al 2013). Tadros et al (2013) demonstrated that the main types of referrals to mental health services from acute hospitals for assessment of mental health and associated risks included; Foley (2013) identified that the RAID model has been instrumental in showing the cost benefits for a mental health service in the acute hospital, suggesting that for every £1 invested in MHLTs £4 is saved.…”
Section: Rapid Assessment Interface and Dischargementioning
confidence: 99%
“…RAID works within the emergency department and inpatient acute wards (Tadros et al 2013). Tadros et al (2013) demonstrated that the main types of referrals to mental health services from acute hospitals for assessment of mental health and associated risks included; Foley (2013) identified that the RAID model has been instrumental in showing the cost benefits for a mental health service in the acute hospital, suggesting that for every £1 invested in MHLTs £4 is saved. Parsonage and Fosey (2011) concluded that the RAID model can save up to £9.5 million per year for the acute hospital, though savings would depend on different sizes of the acute hospitals and the MHLTs commissioned to deliver such a service.…”
Section: Rapid Assessment Interface and Dischargementioning
confidence: 99%
See 1 more Smart Citation